ABC transporter genes ABC-C6 and ABC-G33 alter plant-microbeparasite interactions in the rhizosphere - Cox, D.E.; Dyer, S.; Weir, R.; Cheseto, X.; Sturrock, M.; Coyne, D.; Torto, B.; Maule, A.G.; Dalzell, J.J. (Springer, 2019)
Plants are master regulators of rhizosphere ecology, secreting a complex mixture of compounds into the soil, collectively termed plant root exudate. Root exudate composition is highly dynamic and functional, mediating economically important interactions between plants and a wide range of soil organisms. Currently we know very little about the molecular basis of root exudate composition, which is a key hurdle to functional exploitation of root exudates for crop improvement. Root expressed transporters modulate exudate composition and could be manipulated to develop beneficial plant root exudate traits. Using Virus Induced Gene silencing (VIGS), we demonstrate that knockdown of two root-expressed ABC transporter genes in tomato cv. Moneymaker, ABC-C6 and ABC-G33, alters the composition of semi-volatile compounds in collected root exudates. Root exudate chemotaxis assays demonstrate that knockdown of each transporter gene triggers the repulsion of economically relevant Meloidogyne and Globodera spp. plant parasitic nematodes, which are attracted to control treatment root exudates. Knockdown of ABC-C6 inhibits egg hatching of Meloidogyne and Globodera spp., relative to controls. Knockdown of ABC-G33 has no impact on egg hatching of Meloidogyne spp. but has a substantial inhibitory impact on egg hatching of G. pallida. ABC-C6 knockdown has no impact on the attraction of the plant pathogen Agrobacterium tumefaciens, or the plant growth promoting Bacillus subtilis, relative to controls. Silencing ABC-G33 induces a statistically significant reduction in attraction of B. subtilis, with no impact on attraction of A. tumefaciens. By inoculating selected differentially exuded compounds into control root exudates, we demonstrate that hexadecaonic acid and pentadecane are biologically relevant parasite repellents. ABC-C6 represents a promising target for breeding or biotechnology intervention strategies as gene knockdown leads to the repulsion of economically important plant parasites and retains attraction of the beneficial rhizobacterium B. subtilis. This study exposes the link between ABC transporters, root exudate composition, and ex planta interactions with agriculturally and economically relevant rhizosphere organisms, paving the way for new approaches to rhizosphere engineering and crop protection.